rozwiąż nierównośc 2√6x-3x²-2<0​

Odpowiedź :

[tex]2 \sqrt{6}x - 3 {x}^{2} - 2 < 0[/tex]

[tex] - 3 {x}^{2} + 2 \sqrt{6}x - 2 < 0[/tex]

∆=

[tex] {b}^{2} - 4ac = {(2 \sqrt{6}) }^{2} - 4 \times ( - 3) \times ( - 2) = 24 - 24 = 0[/tex]

[tex] x_{0} = \frac{ - b}{2a} = \frac{ - 2 \sqrt{6} }{2 \times ( - 3)} = \frac{ - 2 \sqrt{6} }{ - 6} = \frac{1}{3} \sqrt{6} [/tex]

Odpowiedź:

Szczegółowe wyjaśnienie:

-3x² + 2√6x - 2 < 0

Δ = 24 - 24 = 0

x = -2√6 / -6 = √6 / 3      podwójny

*załącznik*

x ∈ ℝ \ {√6 / 3}

Zobacz obrazek Matematyk2k01